Safety in the skies : personnel and parties in NTSB aviation accident investigations : master volume - Sarsfield, Liam, 1955-; Stanley, William L.; Lebow, Cynthia C.; Ettedgui, Emile; Henning, Garth; Rand eBooks (Santa Monica, CA : RAND, 2000)
Recent high-profile commercial aviation mishaps have stretched the National Transportation Safety Board's resources to the limit and are testing the agency's ability to unravel the sorts of complex failures that lead to tragic accidents. In recognizing the enormous challenges the NTSB faces, agency Chairman Jim Hall sought a critical examination of the NTSB's ability to investigate major transportation accidents, and in particular commercial aviation accidents. The results of that study are contained in this report, the most comprehensive examination of the workings of the NTSB in the 30-year history of the agency. Adopting a multidisciplinary approach, RAND used a variety of quantitative and qualitative research techniques to assess the NTSB's operations and processes. This research, conducted in RAND's Institute for Civil Justice, outlines recommendations aimed at: strengthening the party process-which involves manufacturers, operators, and others in the determination of the probable cause of an accident; expanding the statement of causation; modernizing the NTSB's investigative procedures and streamlining its internal processes; managing the agency's resources and staffing more effectively; developing training opportunities for NTSB staff; and improving the agency's R&D facilities.
"Institute for Civil Justice."
Includes bibliographical references (p. 299-329).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- National Transportation Safety Board -- Evaluation; Aircraft accidents -- Investigation -- United States; Conflict of interests -- United States; Electronic books